Bienestar ocupacional en el desempeño laboral del personal operativo del Cuerpo de Bomberos del cantón Guaranda, año 2024. - Guamán Aldaz Diana Ayde (2025)
The objective of the research was to determine how occupational well-being affects the work performance of the operational personnel of the Guaranda Fire Department in 2024, using a mixed approach with descriptive and correlational techniques, while the surveys provided quantitative data on well-being and performance, the interviews provided a qualitative analysis of the perceptions of the personnel, and the non-experimental design allowed us to observe the working conditions in their natural context. The results showed that occupational well-being is influenced by factors such as work stress, insufficient material resources, long working hours and lack of psychological support programmes, and a significant correlation was identified between well-being and work performance, with a coefficient of 0.70, indicating that better well-being conditions are associated with more efficient and effective performance in critical situations, however, gaps were found in stress management and access to psychological support, which negatively affects the physical and emotional health of staff. It is concluded that the current working conditions affect both the well-being and performance of operational staff, which increases the risks of burnout, errors and absenteeism, therefore it is recommended to ensure the availability of adequate equipment and to implement psychological support and stress management programmes. Keywords: Occupational well-being, Job performance, Fire Brigade, Working hours, Working conditions.